Violência dirigida aos professores na internet: um estudo na rede social Twitter - Silva, Francisco Valmir da (2016)
This study presents the results of a survey thematized around the manifestation of violence directed at teachers on the internet, considering a cut made on twitter social network. We had as main objective to analyze the content of messages, characterized as violent directed to teachers on twitter. As a theoretical reference was to Levy's contribution (1996, 1999); Arendt (2007; 2009); Recuero (2014); Rock (2012); Zuin (2008a; 2012) and others. This is an exploratory research, with mixed approach: qualitative and quantitative; the used research techniques were content analysis - AC and social network analysis - ARS; the research sample consisted of 2,464 tweets (messages). For the collection, analysis and representation of data, and NodeXL Gephi software were used. was obtained as a result, there are in fact manifestations of violence conveyed in the social network twitter against teachers and these are manifested primarily through terms, words or phrases denoting name-calling, threats and hate manifestation observed in the relationship between teachers and the most recurrent subjects in the messages and ultimately correlate with generating elements present in the classroom, to the occurrence and onset of these expressions of violence against teachers in the social network twitter, the time that was given study.